Reading interest and reading comprehension performance among Indonesian ESP language learners - Musta’aliyah; Siti Suharsih; Sutrisno Sadji Evenddy (Erudita: Journal of English Language Teaching, 2022)
The purpose of the research is to determine whether there is a correlation between students’ reading interest and reading comprehension in the eleventh grade at a public vocational school in Cilegon, Banten, Indonesia. Grounded in quantitative research, the researchers a correlational research design approach. To collect the data, the researchers employed a reading comprehension test and a reading interest questionnaire as the instruments. The researchers applied random cluster sampling, with one class involved as a sample. The class consisted of 31 students. Hypothesis testing by product moment by the SPSS version 26 program revealed that the value of the t-count was higher than the t-table (0.411>0.355). It indicates that the null hypothesis is rejected, but the alternative hypothesis is accepted. The findings also demonstrate that there was a positive correlation between students’ reading interest and reading comprehension in the 11th grade of the vocational school in the moderate category. This study concludes with empirical evidence that if the reading interest decreases, it will be accompanied by a decrease in reading comprehension.